Characterization of chromosomal segment substitution lines developed in the genetic background of rice variety K 343: Chromosomal segment substitution lines of rice - Niharika; Salgotra, R. K.; Sharma, Mamta; Sharma , Richa; Ratnasekera, Disna; Al-Ashkar, Ibrahim; Zaboo, Sadaf Shafi; lone, Javeed Ahmed; Sharma , Manmohan; El Sabagh, Ayman (Cellular and Molecular Biology, 2024)
In this study, BC3F2 convergent population [(K343*3/RML22 × K343*3/DHMAS) × K343] was constructed by marker-assisted backcross breeding using K343 as the recurrent parent. DHMAS and RML22 were used as donor parents for the rice blast resistance genes Pi54 and Pi9, respectively. The population was first characterized using GGT 2.0 software, which showed 96.7% of the recurrent genome recovery covering 13953.6 cM, while DHMAS and RML22 showed 1.6% (235.5 cM) and 1.2% (177.1 cM) introgression respectively. The chromosomal segment substitution lines (CSSLs) were then identified using CSSL Finder software. A total of 36 CSSLs were identified, including 22 for DHMAS/K343 and 14 for RML22/K343. Introgression rates for donor substituted segments in DHMAS/K343 CSSLs ranged from 0.54% to 5.99%, with donor coverage of 44.5%, while in RML22/K343 CSSLs, introgression rates ranged from 0.54% to 4.75%, with donor coverage of 24.5%. The identified CSSLs would be a valuable genetic pool and could be used as genomic resources for the discovery and mapping of important genes and QTLs in rice genetic improvement.